"Learning How to Teach" in Nursing: Perspectives of Clinicians After a Formal Academy. Issue 1 (January 2020) - Jarosinski, Judith M.; Seldomridge, Lisa A.; Reid, Tina P.; Hinderer, Katherine A.
Abstract : Background: The nursing faculty shortage is expected to persist throughout the next decade. Understanding what influences transition from clinician to educator and retention can improve approaches used in nursing programs for those aspiring to careers in nursing education. Purpose: This qualitative study elicited the experiences of participants who completed a structured program to prepare clinicians to become clinical faculty for prelicensure students. Methods: Focus groups uncovered participant perspectives on "learning how to teach." Results: Using interpretive phenomenological analysis, the themes (1) I'm not sure I can do this, (2) changing perspectives-learning to teach, and (3) instilling confidence emerged. Conclusions: Novice educators reported benefitting most from exposure to multiple teaching methods, simulated teaching encounters, and group debriefing as they learned to become educators. Abstract : Supplemental digital content is available in the text.